2004
DOI: 10.1063/1.1691499
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and electronic state of Co in epitaxial anatase CoxTi1−xO2 thin films grown by reactive sputtering

Abstract: The magnetic and phase properties of Co x Ti 1Ϫx O 2 anatase thin films grown epitaxially on ͑001͒ LaAlO 3 by a reactive rf magnetron cosputter deposition have been examined. Co x Ti 1Ϫx O 2 (x ϭ0.07) thin films exhibit room-temperature ferromagnetism, as evidenced by hysteresis in M-H loop. Chemical mapping indicates segregation of the Co dopant atoms in these films. However, x-ray photoelectron spectroscopy suggests that the segregated Co is not metallic, but in the Co ϩ2 state. These results are consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…8). The 2p peak positions and their satellite structures confirm high spin divalent Co [18][19][20]. The spectra deny the presence of Co metallic state, since in that case the Co 2p 3/2 peak would have appeared at [21].…”
Section: Zn 2p Mn 2p and Co 2p Xps Datamentioning
confidence: 66%
“…8). The 2p peak positions and their satellite structures confirm high spin divalent Co [18][19][20]. The spectra deny the presence of Co metallic state, since in that case the Co 2p 3/2 peak would have appeared at [21].…”
Section: Zn 2p Mn 2p and Co 2p Xps Datamentioning
confidence: 66%
“…Few researchers claim that the ferromagnetism in Zn 1Àx Co x O is due to intrinsic effect [13][14][15], while others describe it as an extrinsic effect due to the secondary phases of cobalt oxides and Co metallic clusters [16][17][18][19]. Besides, Khare et al [20] demonstrated that zinc interstitials defects are critical to ferromagnetism rather than oxygen vacancies in Co-doped ZnO.…”
Section: Introductionmentioning
confidence: 98%
“…It can be found that Mn and Si peaks are uniformly distributed across the film surface. If there are Mn clusters, we would expect an enhancement in Mn signal intensity in the precipitates [14]. However, this is not observed.…”
Section: Resultsmentioning
confidence: 56%